Pan-Islamism in Russia 1905-1930 : an analysis of its origins, features an impact - Akhmetova, Elmira (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2014)
The research examines Pan-Islamic movement in Russia between 1905-1930, the main factors behind its appearance, peculiarities and its impact on other leading ideologies of that time such as Pan-Turkism, Pan-Turanism and Muslim National Communism through analyzing the official documents from Tsarist and Soviet sources, records of the All-Russian Muslim Congresses between 1905-1924, as well as the thoughts and activities of Russia's Muslim intellectuals, mainly 'Abd al-Rashīd Ibrahimov, Musa Jārullāh, Ismail Gaspralı and Mir Said Sultan-Galiev. In order to examine the works of Ibrahimov, Jārullāh and Gaspralı, the researcher adopted an inductive and textual analysis method. The research found a huge gap between the official portrait of Pan-Islam, designed by the Tsarist and then enriched by the Soviet authorities, and its real appearance in Russia. The Tsarist gendarmerie and secret service departments defined the entire intellectual, religious, social, educational and political activities of Russia's Muslims after 1905 as 'Pan-Islamism' or 'Pan-Turkism,' an anti-government movement. Yet, as the research exposes, Pan-Islamism in the thoughts of Russia's Muslim intellectuals was formulated as a peaceful ideology, no more than emphasizing the necessity for fraternity and solidarity among all Muslims of the world. Also, the research suggests that the extensive mushrooming of the call for Muslim unity at the beginning of the twentieth century in Russia should not be studied in isolation from the fundamental Islamic thoughts and universal values of Islam such as solidarity, justice, brotherhood and responsibility of the spiritual and political leaders toward other Muslims. Pan-Islamism in a Russian context was an attempt of local Muslims to reinstate the political dimensions of Islam in order to strengthen their legal, economic, religious, social and cultural positions against the danger emanating from Russian Imperialism. Moreover, it establishes that the consideration of Pan-Islamism as an interim period in the universal ideological development of nation formation process and the rise of nationalism is not applicable to the Russian case. Up to the 1920s, the large-scale movement towards unity of all layers of Muslim society of Russia went parallel with the growth of nationalism among the people, who claimed to be firstly Muslim, then Turkic. Also, there was never, in the Russian case, a natural decline in the hold of religion due to the rise of ethnic national awareness. Lastly, the study underlines that the Western classical approach of 'modeling' Europe for every small or big event that occurred in other parts of the world led to the distortion of the original shape of Pan-Islamism in the Western (Russian) scholarship. Thus the research emphasizes on the need for an alternative approach for studying Pan-Islamism, as well as other political and social developments occurring in the Muslim world.